Studi Korelasional Gaya Kepemimpinan Terhadap Sikap Kewirausahaan Karyawan di Penerbit Gramedia Group - Winarno Winarno (Universitas Multimedia Nusantara, 2010)
The objectives of this study is to find out relationship between the leadership style and the Entrapreneurial attitude of the employees. The study was conducted at Gramedia group publishing houses with 60 respondents selected randomly from editorial departements of the companies within the corporate. In accordance with local conditions and pratices in the corporate concerned, the Group makes contributions to various operated policy schemes which cover the majority of employees. The data was analyzed using simple regression analysis, Pearson Product-Moment correlation. The research concluded that there are positive correlations between leadership style and entrapreneurial attitude of the employees. Therefore the leadership style is very important factor in increasing the entapreneurial attitude of the employees. Keywords: Intrapreneurship, leadership style, employees, Gramedia Group Publishing.